A sensitive material and sensor for detecting H2S, a component of SF6 discharge decomposition, and its preparation method and application
By using sensitive materials composed of hexahedral ZnO nanorods and SnS2 debyn nanowires, a high-sensitivity and stability gas sensor for detection of H2S of SF6 discharge decomposition components was prepared, which solved the problems of low detection sensitivity and poor stability in the prior art, and achieved effective detection and rapid response to H2S.
Patent Information
- Application Number
- CN202310205060.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-03-06
AI Technical Summary
The gas sensor used in the prior art for detection of the SF6 discharge decomposition component H2S has low sensitivity, poor stability, and long response recovery time, which leads to huge challenges in practical applications.
A sensitive material composed of hexahedral ZnO nanorods and SnS2 debyn nanowires was used to prepare the H2S gas sensor by dissolving heat method, and the sensitivity and stability of the sensor were improved by using the Debyn size effect and large specific surface area.
It achieves higher sensitivity, better repetitive performance and excellent selectivity. The sensor can effectively detect H2S concentration, and has long-term stability and rapid response recovery time.
Smart Images

Figure CN116399915B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of gas sensors, and in particular relates to a sensitive material and sensor for detecting H2S, a component of SF6 discharge decomposition, and a preparation method and application thereof. Background Art
[0002] Gas Insulated Switchgear (GIS) is a reliable power transmission and transformation equipment, which has been widely used in power transmission at home and abroad. Among them, sulfur hexafluoride (SF6) has excellent insulation and arc extinguishing performance and is widely used in gas insulated switchgear. SF6 electrical insulation equipment has the advantages of small size, compact structure, stable insulation performance, reliable operation, etc., and is widely used in UHV and EHV power systems. Since SF6 electrical insulation equipment will inevitably produce various insulation defects during the manufacturing and operation process, it may induce partial discharge and spark discharge inside the equipment and even cause through-flashover to reduce the insulation performance of electrical equipment, seriously affecting the reliability of safe operation of the power system. Research on SF6 gas decomposition components shows that there is a clear correlation between the internal discharge fault and overheating fault of electrical insulation equipment and the state of SF6 decomposition components. The types, concentrations and gas production rates of SF6 decomposition components corresponding to insulation faults caused by different defect types are not the same. In discharge faults, the discharge of lower energy, such as suspended discharge, corona discharge, and surface discharge, usually triggers the generation of products such as SO2, SOF2, and HF, and the content of the products increases with the severity of the local discharge. After the occurrence of high-energy discharge faults such as arc discharge and spark discharge, the main product that can be detected is SOF2, and trace amounts of SOF4 and SO2F2 can also be detected. H2S, SO2, SOF4, and SO2F2 can usually be detected under the action of local overheating faults. When the solid insulating material is damaged, CO, CO2, and a large amount of CF4 will also be produced. Secondly, with the continuous development of insulation faults inside electrical equipment, the concentration of characteristic gases of SF6 decomposition components will continue to rise. The development time and energy strength of discharge faults and overheating faults can be diagnosed based on the detected gas concentration, so as to judge the degree of deterioration of the insulation inside the electrical equipment and realize the evaluation of the operating status of the electrical equipment, thereby ensuring the safe, stable, and reliable operation of SF6 insulated electrical equipment. Therefore, effective monitoring of typical gases of SF6 discharge decomposition components inside SF6 insulated electrical equipment is of great significance, and can provide an important basis for evaluating the operating status of electrical equipment and diagnosing early latent faults, thereby eliminating insulation faults in a timely manner to avoid huge losses to the national economy and people's lives.
[0003] H2S is a typical gas decomposed by discharge in SF6 insulated electrical equipment. The creation of H2S gas sensors is of great significance for evaluating the operating status of SF6 insulated equipment. At present, no specific research has been carried out on gas sensors for detecting H2S, a component of SF6 discharge decomposition. Gas sensors for H2S detection have low sensitivity, poor stability, and long response recovery time, which leads to huge challenges in practical applications. Therefore, it is necessary to manufacture a new sensor for detecting H2S, a component of SF6 discharge decomposition, to solve the current problems. Summary of the invention
[0004] In view of the shortcomings of the prior art, the present invention proposes a sensitive material and sensor for detecting H2S, a component of SF6 discharge decomposition, and a preparation method and application thereof. A H2S gas sensor with Debye size effect and large specific surface area of hexahedral ZnO nanorods / SnS2 Debye nanowires is prepared by the solution heat method. The sensor for detecting H2S, a component of SF6 discharge decomposition, prepared based on the sensitive material of SnS2 Debye nanowire structure modified by hexahedral ZnO nanorods has higher sensitivity, better repeatability, excellent selectivity and long-term stability.
[0005] In order to solve the above problems, the technical solution adopted by the present invention is:
[0006] A sensitive material for detecting H2S, a component of SF6 discharge decomposition, is composed of hexahedral ZnO nanorods and SnS2 Debye nanowires. The hexahedral ZnO nanorods are hexagonal columns, and the SnS2 Debye nanowires form nanoclusters, which have Debye size effect and large specific surface area.
[0007] A method for preparing a sensitive material for detecting H2S, a component of SF6 discharge decomposition, comprises the following steps:
[0008] (1) SnCl4 was heated to 450°C in an air atmosphere and maintained for 4 h to obtain SnO2 powder, PVP, thiourea and SnO2 were dissolved in deionized water under stirring, the mixed solution was transferred to a polytetrafluoroethylene-lined reactor, maintained at 200°C for 24 h, and the reaction product was centrifuged, washed and dried to obtain SnS2 Debye nanowires;
[0009] (2) Weigh Zn(NO3)2·6H2O and dissolve it in deionized water under stirring for 1 hour, then add NaOH solution to the solution and stir for 30 minutes, transfer the mixed solution to a polytetrafluoroethylene reactor, keep it at 120°C for 12 hours, and centrifuge the reaction product to wash and dry it to obtain hexahedral ZnO nanorods;
[0010] (3) The prepared hexahedral ZnO nanorods and SnS2 Debye nanowires were dissolved in ethanol in a certain ratio, the mixed solution was ultrasonicated for 30 min, and then stirred at 60°C for 12 h to obtain hexahedral ZnO nanorods / SnS2 Debye nanowires.
[0011] Furthermore,
[0012] In (1), the heating rate of SnCl4 in air is 3°C / min;
[0013] The molar ratio of thiourea to SnO2 is 5:2; the concentration of PVP dissolved in deionized water is 3.33 mg / mL;
[0014] The concentration of thiourea dissolved in deionized water is 0.08 mol / L.
[0015] Furthermore,
[0016] In (2), the concentration of Zn(NO3)2·6H2O dissolved in deionized water is 0.015 g / mL;
[0017] The concentration of NaOH is 4 mol / L, and the volume ratio of NaOH to water is 1:7.
[0018] Furthermore,
[0019] The mass ratio of the hexahedral ZnO nanorods to the SnS2 Debye nanowires in (3) is 1%-10%, preferably 5%.
[0020] A sensor for detecting H2S, a component of SF6 discharge decomposition, wherein a sensitive layer is provided in the sensor.
[0021] It also includes interdigital electrodes, and the sensitive layer is prepared by dissolving hexahedral ZnO nanorods / SnS2 Debye nanowires in ethanol and coating them on the surface of the interdigital electrodes.
[0022] Furthermore,
[0023] The sensing principle of the sensor is:
[0024] The sensitive layer of the sensor has a Debye size effect and a large specific surface area, which can meet the adsorption and rapid transfer of electrons when the sensor contacts H2S gas. When the sensor contacts low-concentration H2S, H2S is adsorbed on the surface of the sensitive material, and the rapid transfer of electrons causes the sensor's resistance signal to change. As the H2S concentration increases, H2S contacts more sensitive materials and more adsorption occurs, causing more changes in electrons. When the sensor is out of the H2S gas detection environment, the adsorbed H2S diffuses from the material surface to the low-concentration area, causing the resistance of the sensitive material to return to its initial state.
[0025] A method for preparing a sensor for detecting H2S, a component of SF6 discharge decomposition, comprises the following steps:
[0026] Take an appropriate amount of hexahedral ZnO nanorods / SnS2 Debye nanowire composite material, grind and coat it on the interdigital electrodes to prepare a sensor.
[0027] An application of a sensor for detecting H2S, a component of SF6 discharge decomposition.
[0028] The sensor is used for detecting H2S, a component of SF6 discharge decomposition, and is used for reflecting the operating status of SF6 insulated electrical equipment.
[0029] Furthermore,
[0030] When the sensor is exposed to H2S, electrons at the ZnO-SnS2 heterojunction interface move in opposite directions. When the new Fermi level reaches equilibrium, the depletion layer thickness decreases, causing the sensor's resistance to decrease. In this reaction, the heterojunction acts as a signal amplifier, making it easier to detect trace H2S at sub-ppb sensitivity.
[0031] Furthermore,
[0032] The calculations were performed using PBE, PAW, and GGA in VASP, based on the cutoff energy (400 eV), vacuum layer and k points The material structure is optimized based on the setting data, and the adsorption energy and energy band structure are calculated;
[0033] When the maximum ionic Hermann-Feynman force and the total energy are less than and When , the structural optimization is terminated;
[0034] Adsorption energy E ad The calculation formula is:
[0035] E ad =E ZnO-SnS2 / H2S -E ZnO-SnS2 -E H2S
[0036] E ZnO-SnS2 / H2S is the energy of ZnO-SnS2 adsorbing H2S gas molecules, E ZnO-SnS2 is the energy of the ZnO-SnS2 heterojunction composite material, E H2 is the energy of the H2S gas molecule.
[0037] The invention discloses a sensitive material and sensor for detecting H2S, a component decomposed by SF6 discharge, and its preparation method and application. The invention adopts hexahedral ZnO nanorods and SnS2 Debye nanowires as the sensitive layer of the sensor, and prepares a hexahedral ZnO nanorod / SnS2 Debye nanowire H2S sensor by a simple and easy-to-operate method. The obtained sensor has excellent properties such as low detection limit (50ppb) and fast response recovery time (10s / 51s). The invention detects H2S, a component decomposed by SF6 discharge, by means of a gas sensor, and the test results show that the sensor can effectively detect the concentration of H2S and has good selectivity for H2S. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 The preparation process diagram of the sensor prepared by the hexahedral ZnO nanorods / SnS2 Debye nanowires according to the embodiment of the present invention:
[0039] Figure 2 (a) is the XRD pattern of ZnO (5%)-SnS2 in the embodiment of the present invention;
[0040] (b) is the EDS spectrum of ZnO (5%)-SnS2 in the embodiment of the present invention;
[0041] (cd) are SEM characterizations of ZnO (5%)-SnS2 in different fields of view in the present invention;
[0042] (e) is a general spectrum of element distribution of an embodiment of the present invention;
[0043] (fi) is the distribution diagram of Sn, S, Zn and O elements in the embodiment of the present invention;
[0044] Figure 3 (ab) are TEM images of ZnO(5%)-SnS2 according to the present invention;
[0045] (c) is the HRTEM of ZnO(5%)-SnS2 in the embodiment of the present invention;
[0046] (d) is the electron diffraction pattern (SAED) of ZnO (5%)-SnS2 in the embodiment of the present invention;
[0047] Figure 4 Schematic diagram of the response mechanism of the sensor according to the embodiment of the present invention;
[0048] Figure 5 (a) is the response of different proportions of ZnO composite SnS2 to 30ppm H2S at different working temperatures in the embodiment of the present invention;
[0049] (b) is the response of different proportions of ZnO composite SnS2 to different concentrations of H2S at the optimal working temperature of the embodiment of the present invention;
[0050] (c) is the response of ZnO composite SnS2 with different ratios to H2S concentration gradient at the optimal working temperature of the embodiment of the present invention;
[0051] (d) is the resistance change of different proportions of ZnO (5%)-SnS2 in response to H2S at the optimal working temperature of the embodiment of the present invention;
[0052] (e) is a graph showing the response recovery time of SnS2 composites with different ratios of ZnO to 30 ppm H2S in an embodiment of the present invention;
[0053] (f) is the selectivity of ZnO (5%)-SnS2 to 30ppm of different gases in the embodiment of the present invention;
[0054] Figure 6 (a) is the repeatability test of ZnO-SnS2 exposed to 1ppm, 10ppm, and 20ppm H2S in an embodiment of the present invention; (b) is the resistance of the sensor under different humidity and the response to 30ppm in an embodiment of the present invention;
[0055] (c) The long-term stability of the ZnO-SnS2 sensor of the embodiment of the present invention at 10ppm, 30ppm, and 50ppm;
[0056] (d) is the IV curve of ZnO-SnS2 in different H2S concentrations according to the embodiment of the present invention;
[0057] Figure 7 The H2S sensor prepared by ZnO (5%)-SnS2 detects H2S gas on the SF6 discharge decomposition platform and is used for the evaluation of the operating status of SF6 electrical equipment;
[0058] Figure 8 .(ad) Optimized structures of SnS2, ZnO-SnS2, and SnS2 adsorbing H2S, (e, f) Differential charge density of SnS2 and ZnO-SnS2 heterojunctions adsorbing H2S;
[0059] Fig. 9 (a) Band structure of SnS2; (b) Band structure of ZnO-SnS2 heterojunction; (c) Band structure of SnS2 adsorbing H2S gas; (d) Band structure of ZnO-SnS2 heterojunction adsorbing H2S gas. DETAILED DESCRIPTION
[0060] The specific implementation manner will be further described below in conjunction with the accompanying drawings.
[0061] The reagents and instruments in the following examples are all conventional experimental reagents and instruments.
[0062] Embodiment 1:
[0063] A sensitive material for detecting H2S, a component of SF6 discharge decomposition, is composed of hexahedral ZnO nanorods and SnS2 Debye nanowires. The hexahedral ZnO nanorods are hexagonal columns, and the SnS2 Debye nanowires form nanoclusters, which have Debye size effect and large specific surface area.
[0064] A method for preparing a sensitive material for detecting H2S, a component of SF6 discharge decomposition, comprises the following steps:
[0065] (1) SnCl4 was heated to 450℃ at a rate of 3℃ / min in air atmosphere and maintained for 4h to obtain SnO2 powder. Then, 0.2g PVP, 5mmol thiourea, and 2mmol SnO2 were accurately weighed and dissolved in 60mL deionized water under stirring. The mixed solution was transferred to a 100mL polytetrafluoroethylene-lined reactor and maintained at 200℃ for 24h. The reaction product was centrifuged, washed, and dried to obtain SnS2 Debye nanowires.
[0066] (2) Weigh 1.04 g Zn(NO3)2·6H2O and dissolve it in 70 mL deionized water under stirring, and continue stirring for 1 h. Then add 10 mL NaOH solution (4 mol / L) to the solution and stir for 30 min. Transfer the mixed solution to a 100 mL polytetrafluoroethylene reactor and keep it at 120 °C for 12 h. The reaction product is centrifuged, washed and dried to obtain ZnO nanorods.
[0067] (3) The prepared hexahedral ZnO and SnS2 powders were dissolved in 20 mL of ethanol in a mass ratio of 1%, 5%, and 10%, the mixed solution was ultrasonicated for 30 min, and then stirred at 60°C for 12 h to obtain hexahedral ZnO nanorods / SnS2 Debye nanowires.
[0068] The hexahedral ZnO nanorods / SnS2 Debye nanowires have a large specific surface area and Debye size effect, which enables the gas sensor to have better gas-sensing properties.
[0069] Take an appropriate amount of hexahedral ZnO nanorods / SnS2 Debye nanowire composite material and grind and coat it on the interdigital electrode to perform characterization analysis of the hexahedral ZnO nanorods / SnS2 Debye nanowires:
[0070] Scanning electron microscopy and transmission electron microscopy were used to characterize the structural morphology of H2S gas sensors prepared by hexahedral ZnO nanorods / SnS2 Debye nanowires. X-ray diffraction was used to obtain X-ray diffraction patterns.
[0071] XRD, SEM and EDS characterization of ZnO(5%)-SnS2 Figure 2 shown. Figure 2(a) shows the XRD pattern of ZnO (5%)-SnS2. The characteristic peaks of XRD match the characteristic peaks of JCPDS No. 99-0111 of SnS2 and JCPDS No. 23-0677 of ZnO. The matching of characteristic peaks proves that the prepared material is a ZnO-SnS2 composite material. X-ray energy spectrum further proves that the composite material is composed of Sn, S, Zn, and O elements, such as Figure 2 (b) is shown. Figure 1 In (cd), hexagonal columnar nanorods and clusters can be observed. Figure 2 (e) The total element distribution diagram of the mapping analysis shows that the Zn element is mainly concentrated on the nanorods, and Sn and S are mainly distributed on the nanoclusters. Figure 2 (fi) Displays the distribution of Sn, S, Zn, and O elements in the entire region. It is clearly observed that Sn and S elements are mainly concentrated in the clusters of nanowires. Zn elements are distributed on the nanorods. O elements are distributed in the entire region.
[0072] TEM and HRTEM characterization, such as Figure 3 shown. Figure 3 (a) shows the TEM results of the composite material at a field of view of 50 nm, where the nanowires and larger nanorods are evenly distributed. Figure 3 (b) Yes Figure 3 (a) The result of a local magnification. It is clearly observed that the diameter of the nanorods is about 30nm, and the small nanowires are obviously less than 10nm. The nanowires and nanorods are evenly distributed and intertwined with the nanorods. Figure 3 (c) shows the HRTEM of ZnO (5%)-SnS2. The lattice spacing of ZnO is 0.33nm, corresponding to the ZnO (101) crystal plane. The lattice spacing of SnS2 is 0.28nm, corresponding to the SnS2 (101) crystal plane. The (101) crystal planes of SnS2 and ZnO intersect with each other to form a large number of defect states. Figure 3 The electron diffraction patterns show that SnS2 and ZnO have stable crystal structures.
[0073] The above characterization results illustrate the successful preparation of the sensor sensitive layer ZnO nanorods / SnS2 Debye nanowires for detecting H2S, the decomposition component of SF6 discharge.
[0074] Embodiment 2:
[0075] A gas sensor for detecting H2S, a component of SF6 discharge decomposition, uses ZnO nanorods / SnS2 Debye nanowires as the sensitive layer of the sensor. The sensor has a detection limit of 50 ppb, a response recovery time of 10 s and 51 s, and has high selectivity and long-term stability for H2S in the SF6 discharge decomposition components.
[0076] A method for preparing a gas sensor for detecting H2S, a component of SF6 discharge decomposition Figure 1 As shown, follow these steps:
[0077] (1) SnCl4 was heated to 450℃ at a rate of 3℃ / min in air atmosphere and maintained for 4h to obtain SnO2 powder. Then, 0.2g PVP, 5mmol thiourea, and 2mmol SnO2 were accurately weighed and dissolved in 60mL deionized water under stirring. The mixed solution was transferred to a 100mL polytetrafluoroethylene-lined reactor and maintained at 200℃ for 24h. The reaction product was centrifuged, washed, and dried to obtain SnS2 Debye nanowires.
[0078] (2) Weigh 1.04 g Zn(NO3)2·6H2O and dissolve it in 70 mL deionized water under stirring. Continue stirring for 1 h. Then add 10 mL NaOH solution (4 mol / L) to the solution and stir for 30 min. Transfer the mixed solution to a 100 mL polytetrafluoroethylene reactor and keep it at 120 °C for 12 h. The reaction product is centrifuged, washed and dried to obtain ZnO nanorods.
[0079] (3) The prepared ZnO and SnS2 powders were dissolved in 20 mL of ethanol in a mass ratio of 1%, 5%, and 10%, the mixed solution was ultrasonicated for 30 min, and then stirred at 60 °C for 12 h to obtain ZnO nanorods / SnS2 Debye nanowires.
[0080] (4) Take an appropriate amount of ZnO nanorods / SnS2 Debye nanowires composite material, grind and coat it on the interdigital electrode to prepare a gas sensor.
[0081] Sensing principle of H2S gas sensor prepared by hexahedral ZnO nanorods / SnS2 Debye nanowires:
[0082] There are two different types of depletion layers in the ZnO-SnS2 heterojunction. One is caused by the adsorbed oxygen on the surface of the hexahedral ZnO nanorods and SnS2 nanowires, and the other depletion layer is related to the heterojunction formed by SnS2 and ZnO. The work functions of SnS2 and ZnO are 4.4eV and 5.0eV, respectively, which leads to the formation of a nn heterojunction in the SnS2 layer. For the nn heterojunction ZnO-SnS2, the interface is negatively charged due to the presence of electron traps at the heterojunction interface that capture the electrons in the conduction band on both sides of the interface, such as Figure 4(b) As shown. In order to maintain the condition of electrical neutrality, positively charged depletion layers must be formed on both sides of the interface, causing the energy bands on both sides of the interface to bend upward. When the positively charged ZnO-SnS2 reacts with H2S, due to the presence of traps, the heterojunction is more likely to capture electrons, causing H2S to lose electrons. Schematic diagram of the reaction of ZnO-SnS2 with H2S, as shown in Figure 4 As shown in (a), the reaction process is as follows:
[0083] O2(gas)→O2(ads) (1)
[0084] O2(ads)+e - -→O 2- (ads) (2)
[0085] H2S(gas)+O 2- (ads)→SO2+H2O+e- (3)
[0086] Since SnS2 nanowires have Debye length, the performance of H2S gas sensors is greatly improved. ZnO composite SnS2 forms nn heterojunction, which can effectively achieve rapid electron separation. SEM and TEM show that the diameters of SnS2 Debye nanowires and hexahedral ZnO nanorods are 5-10nm and 50-100nm, respectively. Therefore, the ZnO-SnS2 heterojunction has a large specific surface area. Figure 4 (b) shows that when the ZnO-SnS2 sensor is exposed to H2S, the electrons at the ZnO-SnS2 heterojunction interface move in opposite directions. When the new Fermi level reaches equilibrium, the depletion layer thickness decreases, causing the sensor resistance to decrease. In this reaction, the heterojunction acts as a signal amplifier, making it easier to detect trace H2S with sub-ppb sensitivity.
[0087] Embodiment 3:
[0088] An application of a sensor for detecting H2S, a component of SF6 discharge decomposition.
[0089] The sensor is used for detecting H2S, a component of SF6 discharge decomposition, and is used for reflecting the operating status of SF6 insulated electrical equipment.
[0090] Sensing properties of H2S gas sensor prepared by hexahedral ZnO nanorods / SnS2 Debye nanowires:
[0091] Figure 5(a) shows the response curves of the sensor devices prepared with ZnO composite SnS2 ratios of 1%, 5%, 10% and pure SnS2 in 30ppm H2S as the temperature increases. When the temperature increases from 30℃ to 180℃, the response of the ZnO-SnS2 sensor with different ZnO composite ratios increases with the increase of temperature. When the temperature exceeds 180℃, the response of the sensor begins to decrease. Therefore, the optimal working temperature of the prepared ZnO-SnS2 sensor is 180℃. At the working temperature of 180℃, the responses of SnS2, ZnO (1%)-SnS2, ZnO (5%)-SnS2, and ZnO (10%)-SnS2 are 21.71, 44.85, 71.20, 40.85, and 21.71, respectively. The ZnO-SnS2 sensor shows a law that the response value of the sensor increases with the increase of the composite ratio. When the composite ratio exceeds 5%, the response begins to decrease. This is because the heterojunction effect increases with the increase of the ZnO composite ratio. When the composite ratio increases to 5%, the heterojunction effect is most obvious. At this time, the sensitive material has the most exposed oxygen vacancies, so the material responds best to H2S. In order to further study the performance of the sensor, the response of the ZnO-SnS2 sensor to H2S gas of different concentrations was tested at an operating temperature of 180°C. Figure 5 (b,c). Figure 5 (b) Fitting curve showing the response values of ZnO-SnS2 with different composite ratios as the H2S concentration increases. Figure 5 (c) is the response recovery curve of ZnO-SnS2 with the increase of H2S concentration. It can be found from the figure that the response value gradually increases with the increase of H2S concentration, among which the response value of ZnO (5%)-SnS2 is the largest. The real-time resistance curve of ZnO (5%)-SnS2 with the change of H2S concentration is shown in Figure 5 (d) As shown in Figure 2, the resistance variation range of ZnO(5%)-SnS2 increases with the increase of H2S concentration, which means that the sensor has a gradient response to concentration. When H2S contacts ZnO(5%)-SnS2, the resistance decreases, indicating that part of the electrons of H2S enter the ZnO(5%)-SnS2 composite material. Figure 5 (e) shows the response recovery time curve of SnS2 with different proportions of ZnO to 30ppm H2S. The response times of SnS2, ZnO (1%)-SnS2, ZnO (5%)-SnS2, and ZnO (10%)-SnS2 are 16s, 11s, 10s, and 15s, respectively, indicating that the heterojunction formed by SnS2 and ZnO can shorten the response time, but under the condition of 5% ZnO doping, the material can show better electron adsorption and separation characteristics. Figure 5(f) The ZnO (5%)-SnS2 composite material with the highest response value to H2S was selected to test its selectivity to different gases (H2S, H2, CH4, SO2, CO, SO2F2). The results show that ZnO (5%)-SnS2 has specific selectivity for H2S gas.
[0092] Figure 6 (a) shows three consecutive repeated experiments of the ZnO (5%)-SnS2 sensor at H2S concentrations of 1ppm, 10ppm, and 20ppm. The results show that the baseline resistance of the sensor tends to be stable and the response value of the three repeated experiments changes little, which means that the sensor has excellent repeatability. Figure 6 (b) shows the response of the sensor to 30ppmH2S under different humidity conditions. The resistance and response value of the sensor fluctuate slightly within 2%. The change in humidity hardly changes the response characteristics of the sensor. Therefore, the sensor has good moisture resistance. In the long-term stability test of up to 30 days, the response value of the material to different concentrations of H2S (10, 30, 50ppm) varies within less than 3%, as shown in Figure 2. Figure 6 (c) As shown. Therefore, the sensor has long-term stability and can detect H2S gas for a long time. Figure 6 In (d), the in-situ IV curve of the ZnO (5%)-SnS2 sensor was tested for different concentrations of H2S. The slope of the IV curve increases with the increase of H2S concentration, indicating that the conductivity of the material increases with the increase of H2S concentration, which means that the electrons obtained by the material from the H2S system increase with the increase of H2S concentration. This result is consistent with Figure 6 The results of (d) are consistent.
[0093] Figure 7 The H2S sensor prepared for ZnO (5%)-SnS2 detects H2S gas on the SF6 discharge decomposition platform and is used for the evaluation of the operating status of SF6 electrical equipment.
[0094] Example 4
[0095] Density functional theory (DFT) analysis of ZnO-SnS2 adsorption was performed based on VASPV (Vienna Ab-initio Simulation Package), and the calculation parameters were set as follows: cutoff energy (400 eV), vacuum layer and k points When the maximum ionic Hermann-Feynman force and the total energy are less than and When , the structural optimization is terminated.
[0096] Adsorption energy E ad The calculation formula is:
[0097] E ad =E ZnO-SnS2 / H2S -E ZnO-SnS2 -E H2S
[0098] E ZnO-SnS2 / H2S is the energy of ZnO-SnS2 adsorbing H2S gas molecules, E ZnO-SnS2 is the energy of ZnO-SnS2 heterojunction composite material, E H2S is the energy of H2S gas molecule.
[0099] The optimized structure of ZnO-SnS2 based on VASP and the adsorption energy calculation results based on the optimized structure are shown in Figure 8 shown. Figure 8 The optimized structural model of ZnO-SnS2 heterojunction adsorbing H2S is shown. The heterostructure model of SnS2 and ZnO-SnS2 is shown in Figure 2. Figure 8 (ab) as shown. Figure 8 In (cd), the optimized structures of SnS2 and ZnO-SnS2 heterojunction for H2S adsorption are shown. ad is -0.02eV. The distance between SnS2 and H2S molecules is E of H2S adsorption on ZnO-SnS2 ad is -0.38eV. The distance between ZnO-SnS2 and H2S gas molecules is ZnO significantly enhances the adsorption performance of SnS2 for H2S. The differential charge density of SnS2 and ZnO-SnS2 for H2S adsorption is shown in Figure 8 (ef) is shown. Red represents electron-rich areas, and blue represents electron-deficient areas. When SnS2 adsorbs H2S, it is observed that the electrons are mainly located on the surface of SnS2. This phenomenon shows that the electrons lost by H2S are mainly obtained by S atoms on the surface of SnS2 during the process of SnS2 adsorbing H2S. The ZnO-SnS2 heterojunction mainly adsorbs H2S electrons at the heterojunction interface and the ZnO surface. This shows that the heterojunction interface participates in the entire adsorption process of ZnO-SnS2 adsorbing H2S. Using Bader charge analysis, it was found that SnS2 and ZnO-SnS2 obtained 0.003eV and 0.128eV electrons from H2S, respectively, when adsorbing H2S, indicating that the ZnO-SnS2 heterojunction enhances the electron transfer ability. SnS2 and ZnO-SnS2 obtain electrons when adsorbing H2S, resulting in an increase in their conductivity, which proves the experimental result that the resistance of the ZnO-SnS2 sensor decreases when adsorbing H2S.
[0100] Fig. 9 This is the energy band structure of SnS2 and ZnO-SnS2 adsorbing H2S. Fig. 9(a, b) are the band structure curves of SnS2 and ZnO-SnS2 heterojunctions. The band gap of SnS2 is 1.58eV, and the band gap of ZnO-SnS2 is 0.36eV. ZnO forms a typical nn heterojunction after SnS2 is compounded, which reduces the band gap of ZnO-SnS2, making it easier for electrons to transition and form potential wells that are easier to capture electrons. The band gap of SnS2 and ZnO-SnS2 decreases after H2S is adsorbed, such as Fig. 9 (c, d) shows that when SnS2 adsorbs H2S, more electrons enter the valence band, making the band gap narrower.
[0101] The above embodiments are only for illustrating the technical concept and features of the present invention, and their purpose is to enable ordinary technicians in the field to understand the content of the present invention and implement it accordingly, and they cannot be used to limit the protection scope of the present invention. Any equivalent changes or modifications made based on the essence of the content of the present invention should be included in the protection scope of the present invention.
Claims
1. A sensitive material for detecting H2S, a component of SF6 discharge decomposition, characterized by: It is composed of hexahedral ZnO nanorods and SnS2 Debye nanowires. The hexahedral ZnO nanorods are hexagonal columns, and the SnS2 Debye nanowires form nanoclusters. The preparation steps include: (1) SnCl4 was heated to 450℃ in air atmosphere and calcined for 4 h to obtain SnO2 powder. The surfactant PVP, thiourea and SnO2 were dissolved in deionized water under stirring. The mixed solution was transferred to a polytetrafluoroethylene-lined reactor and kept at 200℃ for 24 h. The reaction product was centrifuged, washed and dried to obtain SnS2 Debye nanowires. (2) Weigh Zn(NO3)2•6H2O and dissolve it in deionized water under stirring for 1 h. Then add NaOH solution to the solution and stir for 30 min. Transfer the mixed solution to a polytetrafluoroethylene reactor and keep it at 120°C for 12 h. Centrifuge the reaction product, wash it, and dry it to obtain hexahedral ZnO nanorods. (3) The prepared hexahedral ZnO nanorods and SnS2 Debye nanowires were dissolved in ethanol in a certain ratio, the mixed solution was sonicated for 30 min, and then stirred at 60 °C for 12 h to obtain hexahedral ZnO nanorods / SnS2 Debye nanowires; The mass ratio of hexahedral ZnO nanorods to SnS2 Debye nanowires is 1%-10%.
2. The method for preparing a sensitive material for detecting H2S, a component of SF6 discharge decomposition, according to claim 1, characterized in that: The preparation steps include: (1) SnCl4 was heated to 450℃ in air atmosphere and calcined for 4 h to obtain SnO2 powder. The surfactant PVP, thiourea and SnO2 were dissolved in deionized water under stirring. The mixed solution was transferred to a polytetrafluoroethylene-lined reactor and kept at 200℃ for 24 h. The reaction product was centrifuged, washed and dried to obtain SnS2 Debye nanowires. (2) Weigh Zn(NO3)2•6H2O and dissolve it in deionized water under stirring for 1 h. Then add NaOH solution to the solution and stir for 30 min. Transfer the mixed solution to a polytetrafluoroethylene reactor and keep it at 120°C for 12 h. Centrifuge the reaction product, wash it, and dry it to obtain hexahedral ZnO nanorods. (3) The prepared hexahedral ZnO nanorods and SnS2 Debye nanowires were dissolved in ethanol in a certain ratio, the mixed solution was ultrasonicated for 30 min, and then stirred at 60 °C for 12 h to obtain hexahedral ZnO nanorods / SnS2 Debye nanowires.
3. The method for preparing a sensitive material for detecting H2S, a component of SF6 discharge decomposition, according to claim 2, characterized in that: In (1), the heating rate of SnCl4 in air is 3°C / min; The molar ratio of thiourea to SnO2 is 5:2; the concentration of PVP dissolved in deionized water is 3.33 mg / mL; The concentration of thiourea dissolved in deionized water is 0.08 mol / L.
4. The method for preparing a sensitive material for detecting H2S, a component of SF6 discharge decomposition, according to claim 2, characterized in that: In (2), the concentration of Zn(NO3)2•6H2O dissolved in deionized water is 0.015 g / mL; The concentration of NaOH is 4 mol / L, and the volume ratio of NaOH to water is 1:
7.
5. The method for preparing a sensitive material for detecting H2S, a component of SF6 discharge decomposition, according to claim 2, characterized in that: The mass ratio of the hexahedral ZnO nanorods to the SnS2 Debye nanowires in (3) is 1%-10%.
6. A sensor for detecting H2S, a component of SF6 discharge decomposition, wherein a sensitive layer is provided in the sensor, wherein the sensitive layer is composed of the sensitive material according to claim 1, or the sensitive layer is prepared by the sensitive material prepared by the preparation method according to any one of claims 2 to 5, wherein: It also includes interdigital electrodes, and the sensitive layer is prepared by spin coating the sensitive material on the surface of the interdigital electrodes.
7. The method for preparing a sensor for detecting H2S, a component of SF6 discharge decomposition, according to claim 6, characterized in that: The preparation steps include: A proper amount of sensitive material is spin-coated on 5 pairs of interdigital electrodes to prepare a sensor, and the width of the interdigital electrodes is 100 microns.
8. An application of a sensor for detecting H2S, a component of SF6 discharge decomposition, according to claim 6, characterized in that: The sensor is used for detecting H2S, a component of SF6 discharge decomposition, and is used for reflecting the operating status of SF6 insulated electrical equipment.
Citation Information
Patent Citations
Gas sensitive material based on Zn-doped stannous sulfide, preparation method of gas sensitive material and application of gas sensitive material in detection of methanol
CN112578001A
Tin sulfide / tin disulfide heterojunction material and preparation method thereof
CN113278948A